STEM-PBL Instructional Materials to Support Quality Education through Chemical Literacy in Thermochemistry - Dwy Puspita Sari; Mutiara Agustina Nst; Ani Sutiani; Ratu Evina Dibyantini; Alfira Julian Pratiwi (Jurnal Penelitian Pendidikan IPA, 2026)
The purpose of this study was to evaluate the effectiveness of STEM-Problem Based Learning (STEM-PBL) instructional materials in improving students’ chemical literacy on thermochemistry topics. This study employed a quasi-experimental method using a pretest-posttest control group design. The participants were 56 Chemistry Education students divided into an experimental class and a control class, each consisting of 28 students. Data were collected using a validated and reliable essay test (Cronbach’s α = 0.85). The results showed that the experimental class improved from 36.11 to 88.50, while the control class improved from 31.50 to 78.43. An independent samples t-test revealed a significant difference between the two groups (p < 0.05). In addition, the effect size analysis yielded a Cohen’s d value of 1.16, indicating a large effect. These findings suggest that STEM-PBL instructional materials effectively improve students’ chemical literacy, particularly in conceptual understanding, critical thinking, and problem-solving related to thermochemistry. In conclusion, STEM-PBL instructional materials are effective and feasible for enhancing chemical literacy and supporting quality, contextual, and 21st-century-oriented chemistry learning at the university level.